1983
DOI: 10.1136/bjo.67.11.737
|View full text |Cite
|
Sign up to set email alerts
|

Unusual features in the conjunctiva and cornea of the normal guinea-pig: clinical and histological studies.

Abstract: SUMMARY Clinical and histological studies of the outer eyes of newborn and adult female guineapigs were carried out together with histological studies of fetal eyes. Fine superficial corneal vessels, extending from the limbus, were seen in most newborn and adult eyes and were also present in histological preparations of fetal eyes. These vessels were therefore considered to be features of the normal guinea-pig eye. Masses of tissue composed of lymphoid cells, which were often organised into germinal centres, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 6 publications
7
12
0
Order By: Relevance
“…Because of its histological appearance, the conjunctiva was divided into four zones. Several authors graded the conjunctiva of guinea pigs, 13–18 rats, 19 and mice 20 in a different way to ours; however, in the study by Gasser et al. , 9 the zoning system in guinea pigs was reported similar to ours.…”
Section: Discussionsupporting
confidence: 62%
“…Because of its histological appearance, the conjunctiva was divided into four zones. Several authors graded the conjunctiva of guinea pigs, 13–18 rats, 19 and mice 20 in a different way to ours; however, in the study by Gasser et al. , 9 the zoning system in guinea pigs was reported similar to ours.…”
Section: Discussionsupporting
confidence: 62%
“…The regular occurrence of follicles, most of which are secondary ones with a bright germinal centre indicating lymphoid cell proliferation after antigen contact, were found in the conjunctiva of species such as the guinea‐pig (McMaster et al. 1967; Dwyer et al. 1983), rabbit (Axelrod & Chandler, 1979; Franklin & Remus, 1984; Knop & Knop, 1996a), turkey (Fix & Arp, 1989), chicken (Fix & Arp, 1991) and monkey (Ruskell, 1995b).…”
Section: Lymphatic Cells At the Ocular Surface And Appendagementioning
confidence: 99%
“…Guinea pigs have a remarkably low corneal sensitivity (or a high pressure threshold is needed to elicit a blink), replicated in 3 studies. 1,3,4 In these studies, the guinea pig was observed to have limited to no reflex tearing, which may be a component of the lack of corneal sensitivity ( Fig. 1, Table 1).…”
Section: Normal Anatomymentioning
confidence: 85%
“…Fine superficial corneal neovascularization (usually extending from limbus axially to the first or second third of the cornea) has been reported as a normal finding in fetal, newborn, and adult guinea pigs. 1 However, a later confocal microscopy study did not confirm this. 2 Small palpebral conjunctival outpouchings were noted in the upper and lower fornices in almost all examined animals according to Dwyer and colleagues (1983), and were determined via histology to be masses of lymphoid tissue.…”
Section: Normal Anatomymentioning
confidence: 90%
See 1 more Smart Citation